The aesthetic of the Irish lyric : W.B. Yeats and Derek Mahon - Chia, Joanne Weiting (2015)
This thesis shows how the lyric is the chosen poetic mode in the mature work of W.B. Yeats and is a symbolism whose influence is shown in the work of Derek Mahon. The lyric grants freedom from representation, by showing that the priority of its discourse or aesthetic is ensured through the resistance of ‘nature’ that is implied in the poetic genre. Therefore, this is what the lyric imparts: the aesthetic emotion that defines the poetic medium. This awareness of what the lyric is suggests a complex interaction with reality. Yeats, in particular, demonstrates the epistemological crisis of the lyric as being embodied in aesthetic discourse. Therefore, he shows the importance of the consideration of the very language of the lyric – beyond its representation within a dogmatic understanding of tradition present in the idea of the Romantic lyric. For Mahon, the mode of feeling that the lyric represents proposes a case for, or defense of, the eternal character of poetry. As such, it is threatened by its history as much as the Romantic lyric was by ‘nature,’ through which Mahon appears to discern the crisis of contemporary poetry in the need to establish a reason for the continuation of the poetic tradition. The ‘Irish lyric,’ then, stands for the respective poets’s committment to the lyric form in their work, whose implications in terms of theme or subject matter are considered in this dissertation. I am concerned with the conditions for an aesthetic of the ‘Irish lyric,’ as seen in these poets who represent it, against a pressing political reality that is both within and without for the modern or contemporary poet.